Enhanced recovery in type A aortic dissection evaluating the efficacy and feasibility of early myocardial reperfusion - Niu, Tianyu; Liu, Zhishuo; Liu, Yu; Yang, Zhonglu; Ge, Yuguang; Wang, Lu; Xia, Lin; Jiang, Hui (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThis study investigates the feasibility and early outcomes of early myocardial reperfusion in patients with type A aortic dissection (TAAD), evaluating its effectiveness and potential benefits compared to traditional cardioplegic arrest techniques.MethodsA retrospective analysis was conducted on 168 patients diagnosed with TAAD who underwent surgery at the General Hospital of the Northern Theater Command in China from January 2021 to July 2024. Patients were divided into two groups: early myocardial reperfusion (EMR group, n = 66) and cardioplegic arrest (CA group, n = 102). Perioperative outcomes were compared between the groups.ResultsEarly myocardial reperfusion significantly reduced ventilation time 23.08 (18.21, 66.74) hours vs. 48.58 (19.18, 122.97) hours, P < 0.05], ICU stay time [58.80 (21.20, 126.68) hours vs. 84.86 (41.12, 168.81) hours, P < 0.05], and hospitalization time [13.00 (10.00, 16.00) days vs. 15.00 (11.75, 19.00) days, P < 0.05] compared to the CA group. There was no significant difference in hospital costs, first-hour chest tube drainage, left ventricular ejection fraction, or postoperative adverse events between the groups, except for the rate of CRRT treatment, where the EMR group had significantly fewer patients requiring postoperative CRRT (10.6% vs. 23.5%, P < 0.05).ConclusionThis study demonstrates that early myocardial reperfusion is a feasible and effective technique for TAAD, offering considerable advantages in reducing ventilation time, ICU stay, hospitalization duration and postoperative renal insufficiency.